Transcriptome comparison reveals key candidate genes responsible for the unusual reblooming trait in tree peonies. - Hua Zhou (Public Library of Science (PLoS), 2013)
Tree peonies are important ornamental plants worldwide, but growing them can be frustrating due to their short and concentrated flowering period. Certain cultivars exhibit a reblooming trait that provides a valuable alternative for extending the flowering period. However, the genetic control of reblooming in tree peonies is not well understood. In this study, we compared the molecular properties and morphology of reblooming and non-reblooming tree peonies during the floral initiation and developmental processes. Using transcriptome sequencing technology, we generated 59,275 and 63,962 unigenes with a mean size of 698 bp and 699 bp from the two types of tree peonies, respectively, and identified eight differentially expressed genes that are involved in the floral pathways of Arabidopsis thaliana. These differentially regulated genes were verified through a detailed analysis of their expression pattern during the floral process by real time RT-PCR. From this combined analysis, we identified four genes, PsFT, PsVIN3, PsCO and PsGA20OX, which likely play important roles in the regulation of the reblooming process in tree peonies. These data constitute a valuable resource for the discovery of genes involved in flowering time and insights into the molecular mechanism of flowering to further accelerate the breeding of tree peonies and other perennial woody plants.